A presença das crianças migrantes haitianas nas escolas de Sinop/MT: o que elas visibilizam da escola? - Alexandre, Ivone Jesus (2019)
This study, linked to the Sociology of Childhood research line of the Post-Graduate Program in Sociology of the Federal University of São Carlos, sought to understand how the insertion of Haitian children in the public schools of Sinop / MT is happening. The research objectives were to analyze how the migrant children inserts in the school; to find out what the foreigner shows from school and how the presence of the black migrant children make visible the racialization in the school. The methodology used is based on the ethnographic perspective and the methodological procedures were: observations and individual and group interviews with the Haitian children, the parents, teachers, child development techniques and scholarship recipients. The temporal cut included migrant children who came with their parents from 2015 and 2016 to Brazil, to the city of Sinop in Mato Grosso. It was based the theoretical studies on the sociology of childhood, the concept of differences and racial relations, authors such Oliveira and Abramowicz (2010), Abramowicz et al. (2003, 2009, 2011, 2015), Abramowicz (2011), André (2016), Sarmento (2015), Delgado and Muller (2005), Corsaro (2006), Hall (2003, 2014), Woodward (2014) and Louro (2008). About migrant children I had support in Oliveira (2014), Demartini (2004, 2006, 2011), Martuscelli (2015) Siller (2011), Freitas and Silva (2015) among others. About contemporary migration, specifically the Haitian migration to Sinop, the history of Sinop colonization, the history of Haiti and its political emancipation, gave support to the dialogue, among others, the researches of Cotinguiba and Pimentel (2014), Guimarães (2017); Seitenfus (2015), Seguy (2014), Joanoni Neto (2014); Souza (2009, 2011); Thomaz (2010, 2011) Trouillot (2016) e James (2009). The research results point that the impact that Haitian migrant children presence cause in schools occurs because they are perceived by teachers and peers as different and these differences are explicit in their bodies. It is these differences that make visible the way in which the school racializes the migrant children by establishing a hierarchy among the children themselves and within that hierarchy the Haitian children are subaltern. Thus, schools never revise their racist practices and speeches, they cannot take the children’s color off.